Topographic analysis of the skull vibration-induced nystagmus test with piezoelectric accelerometers and force sensors. Issue 5 (23rd March 2016) - Dumas, Georges; Lion, Alexis; Perrin, Philippe; Ouedraogo, Evariste; Schmerber, Sébastien
Abstract : Vibration-induced nystagmus is elicited by skull or posterior cervical muscle stimulations in patients with vestibular diseases. Skull vibrations delivered by the skull vibration-induced nystagmus test are known to stimulate the inner ear structures directly. This study aimed to measure the vibration transfer at different cranium locations and posterior cervical regions to contribute toward stimulus topographic optimization (experiment 1) and to determine the force applied on the skull with a hand-held vibrator to study the test reproducibility and provide recommendations for good clinical practices (experiment 2). In experiment 1, a 100 Hz hand-held vibrator was applied on the skull (vertex, mastoids) and posterior cervical muscles in 11 healthy participants. Vibration transfer was measured by piezoelectric sensors. In experiment 2, the vibrator was applied 30 times by two experimenters with dominant and nondominant hands on a mannequin equipped to measure the force. Experiment 1 showed that after unilateral mastoid vibratory stimulation, the signal transfer was higher when recorded on the contralateral mastoid than on the vertex or posterior cervical muscles ( P <0.001). No difference was observed between the different vibratory locations when vibration transfer was measured on vertex and posterior cervical muscles. Experiment 2 showed that the force applied to the mannequin varied according to the experimenters and the handedness, higher forces being observed with the most experienced experimenter and with the dominant hand (10.3±1.0 and 7.8±2.9 N, respectively). The variation ranged from 9.8 to 29.4% within the same experimenter. Bone transcranial vibration transfer is more efficient from one mastoid to the other mastoid than other anatomical sites. The mastoid is therefore the optimal site for skull vibration-induced nystagmus test in patients with unilateral vestibular lesions and enables a stronger stimulation of the healthy side. In clinical practice, the vibrator should be placed on the mastoid and should be held by the clinician's dominant hand.